Symptomatology, prognosis and clinical findings of STEMI as a ramification of COVID-19: A systematic review and proportion meta-analysis. (April 2022) - Jaiswal, Vikash; Almas, Talal; Peng Ang, Song; David Song,; Shama, Nishat; Storozhenko, Tatyana; Lnu, Kriti; Parmar, Garima; Qaiser, Saria; Naz, Sidra; Jaiswal, Akash; Malik, Jahanzeb
Abstract: Background: There is an increasing COVID-19 population with concurrent STEMI. SARS-CoV-2 poses a significant risk of hypercoagulable and/or prothrombotic events due to the disturbance in hemostasis by affecting all three components of the Virchow's triad. These abnormalities in hemostasis are an increased risk factor for cardiovascular events, including acute thrombotic occlusion of coronary arteries leading to myocardial infarction. Objective: The objective of this study is to collate the prognosis, symptomatology and clinical findings of COVID-19 adverse events causing STEMI. Methods: Databases were queried with various keyword combinations to find applicable articles. Cardiovascular risk factors, symptomatology, mortality and rates of PCI were analyzed using random-effect model. Results: 15 studies with a total of 379 patients were included in the final analysis. Mean age of patients was 62.82 ± 36.01, with a male predominance (72%, n = 274). Hypertension, dyslipidemia and diabetes mellitus were the most common cardiovascular risk factors among these patients, with a pooled proportion of 72%, 59% and 40% respectively. Dyspnea (61%, n = 131) was the most frequent presenting symptom, followed by chest pain (60%, n = 101) and fever (56%, n = 104). 62% of the patients had obstructive CAD during coronary angiography. The primary reperfusion method used in the majority of cases was percutaneous coronary intervention (64%, n = 124). Mortality, which is the primary outcome in our study, was relatively high, with a rate of 34% across studies. Conclusion: Our findings show that most cases have been found in males, while the most common risk factors were Hypertension and Diabetes Mellitus. In most COVID-19 cases with ST-segment myocardial infarction, most hospitalized patients underwent primary percutaneous coronary intervention instead of fibrinolysis. The in-hospital mortality was significantly higher, making this report significant. As the sample size and reported study are considerably less, it warrants a further large-scale investigation to generalize it. Highlights: 1) There is an increasing COVID-19 population with concurrent STEMI. SARS-CoV-2 poses a significant risk of hypercoagulable and/or prothrombotic events due to the disturbance in hemostasis by affecting all three components of the Virchow's triad. 2) Our findings show that most cases have been found in males, while the most common risk factors were Hypertension and Diabetes Mellitus. 3) The in-hospital mortality was significantly higher, making this report significant.